Allergic Components of Eosinophilic Esophagitis - Spergel, Jonathan (J Allergy Clin Immunol, 2018)
Eosinophilic esophagitis (EoE) is a disorder of increasing prevalence worldwide causing clinical symptoms of vomiting, failure to thrive, and dysphagia and complications of esophageal remodeling with strictures and food impactions. Molecular profiling demonstrates EoE to be an eosinophil predominant disorder with a Th2 cytokine profile reminiscent of other allergic diseases such as asthma, allergic, rhinitis, and atopic dermatitis. Environmental antigens in the form of foods and aeroallergens induce eosinophil, basophil, mast cell, and T cell infiltration. Pathogenesis depends on local epithelial immune activation with production of thymic stromal lymphopoeitin (TSLP) and eotaxin-3. Complications mirror asthmatic airways pathogenesis with increases in subepithelial collagen deposition, angiogenesis, and smooth muscle hypertrophy. The removal of instigating antigens, especially foods, causes disease resolution in >50% of adults and children. The prevalence of concurrent atopic disorders in patients with EoE and the need to control antigen-specific Th2 inflammation underscore the importance of testing for allergens and treating the entire atopic individual to control the potential interplay between organ specific allergic responses.